EMPLOYER BRANDING AND TALENT RETENTION: A COMPARATIVE STUDY OF GEN Z AND MILLENNIALS IN THE POST-PANDEMIC WORKPLACE - Mukhtorov Abdurakhmon Shavkatovich (Modern American Journals, 2025)
This study examines the evolving dynamics of employer branding and talent retention strategies targeting Generation Z (Gen Z) and Millennials in the post-pandemic workplace. As these two cohorts increasingly dominate the global workforce, understanding their distinct values, expectations, and behaviors is crucial for organizations aiming to attract and retain top talent. Drawing on recent surveys and research from 2024-2025, this article highlights key generational differences and similarities, the impact of technological advances such as generative AI, and the implications for employer branding and retention policies.